Unveiling the unseen: Parental experiences in nurturing children with intellectual disabilities: A systematic review - Sophia Euodia Anggoh; Yossie Susanti Eka Putri; Achir Yani Syuhaimie Hamid; Ria Utami Panjaitan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Parents of children with intellectual disabilities face a lifelong caregiving responsibility with multidimensional burdens, including chronic stress, financial pressure, and limited culturally sensitive mental health support. Previous studies have focused more on psychological aspects, so the holistic understanding of resilience and cultural dynamics is still limited. Purpose: To examine the experiences of parents in caring for children with intellectual disabilities Method: Literature search using PRISMA guidelines on PubMed, ScienceDirect, and Google Scholar (2015–2025) with related keywords. Quantitative studies on caregivers of children with intellectual disabilities were selected, while non-parents and non-intelectual disability were excluded. Study selection and methodological quality assessment (Joanna Briggs Institute checklist) were conducted by more than one researcher. Narrative synthesis was applied due to the heterogeneity of the data. Results: Analysis of 10 studies (2,473 participants) revealed high emotional burdens (stress and anxiety) due to children's behavior, stigma, and lack of support. Resilience strategies such as mindful parenting and recreational activities enhance parent-child bonding and self-efficacy. Culture influences coping mechanisms, while father involvement is often hindered by traditional norms. Compared to previous reviews, these findings emphasize cross-cultural resilience and the urgency of community-based gender-inclusive interventions. Conclusion: Caregivers of children with intellectual disabilities demonstrate resilience despite facing complex challenges. Interventions need to integrate psychosocial training, community support, as well as culturally sensitive policies and father participation.